2022
DOI: 10.3390/ijerph19084728
|View full text |Cite
|
Sign up to set email alerts
|

Crisis Work Embedded in a Global Crisis: The Early Phase Impact of COVID-19 on Survivors of Intimate Partner Violence and Service Provisions

Abstract: COVID-19, as a global pandemic, was a public health inflection point for individuals affected by intimate partner violence (IPV) and those who provide IPV services. Public health guidelines that were intended to reduce risk of exposure to the virus impacted vulnerability factors for IPV survivors and associated systems of services. We aimed to (1) explore the effect of COVID-19 on survivors of IPV; (2) assess the effect of COVID-19 on IPV-related service provisions and service providers; and (3) explore challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
1
6
0
7
Order By: Relevance
“…As our findings above demonstrate—and in alignment with similar studies (Garcia et al, 2022; Lipp & Johnson, 2022; Murugan et al 2022; Renov et al, 2022; Shadik et al, 2023; Toros et al, 2023)—street-level bureaucrats in the antiviolence sector faced nearly identical pandemic-era challenges across regional and temporal contexts. We hesitate to think in terms of universality (and what that categorization might flatten) but want to emphasize the power of this similarity for solidarity.…”
Section: Conclusion: What Will Antiviolence Work Be Post-covid-19?supporting
confidence: 88%
“…As our findings above demonstrate—and in alignment with similar studies (Garcia et al, 2022; Lipp & Johnson, 2022; Murugan et al 2022; Renov et al, 2022; Shadik et al, 2023; Toros et al, 2023)—street-level bureaucrats in the antiviolence sector faced nearly identical pandemic-era challenges across regional and temporal contexts. We hesitate to think in terms of universality (and what that categorization might flatten) but want to emphasize the power of this similarity for solidarity.…”
Section: Conclusion: What Will Antiviolence Work Be Post-covid-19?supporting
confidence: 88%
“…There have been few primary studies on this topic, which might explain this ( Garcia et al, 2022 ). Several emerging studies, however, have examined the early-phase impacts of COVID-19 on domestic and family violence service provisions in multiple countries ( Carrington et al, 2021 ; Johnson et al, 2020 ; Murugan et al, 2022 ). These studies explored the views and experiences of service providers and practitioners on how they have adapted to changes in DV service delivery during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…A brief review of the available studies revealed that four major service adaptations and changes have occurred across countries as a result of COVID-19, involving the shift toward remote service provision ( Carrington et al, 2021 ; Cortis et al, 2021 ; Riddell & Haighton, 2022 ; Sapire et al, 2022 ; Voth Schrag et al, 2022 ; Wood et al, 2022 ), a reduction in overall service capacity ( Cortis et al, 2021 ; Wood et al, 2022 ), inter-agency collaborations ( Garcia et al, 2022 ; Murugan et al, 2022 ; Riddell & Haighton, 2022 ), and the provision of limited DV services to historically oppressed or marginalized groups ( Garcia et al, 2022 ; Sapire et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…(interview 11/25/20) There was a belief that if service providers did not provide this aid for clients, no one would. Especially given their client base-some of whom were undocumented or non-native English speakers-this extra labor and its risks were easily rationalized away due to the reality of COVID-19 supports ignoring already marginalized populations (Murugan et al, 2022;Page & Flores-Miller, 2021;Tsui et al, 2022).…”
Section: Adding More To Caseloadsmentioning
confidence: 99%